Predictive factors of visual and anatomical outcome after intravitreal bevacizumab treatment of neovascular age-related macular degeneration: an optical coherence tomography study. Issue 10 (24th June 2009) - Singh, R P; Fu, E X; Smith, S D; Williams, D R; Kaiser, P K
Abstract : Aim: To evaluate the baseline visual and optical coherence tomography (OCT) factors on outcomes after intravitreal bevacizumab treatment of subfoveal neovascular age-related macular degeneration (AMD). Methods: A retrospective analysis of 73 eyes treated with intravitreal bevacizumab for subfoveal neovascular AMD was performed. Change in best corrected Snellen visual acuity (BCVA) and central retinal thickness (CRT) on OCT were the primary outcomes. Automated and manual measurements were made for all OCT characteristics. Results: Seventy-three (100%) and 58 (79.5%) eyes were followed for 3 and 6 months, respectively. The mean BCVA improved from 20/177 to 20/160 (p = 0.03) at 3 months and to 20/143 (p = 0.04) at 6 months. The mean CRT decreased 93 µm (p<0.0001) and 105 µm (p<0.0001) at 3 and 6 months, respectively. Baseline BCVA worse than 20/100 was associated with greater visual improvement (p⩽0.04). Eyes with baseline CRT greater than 400 µm experienced a greater mean CRT reduction (p<0.05). Treatment-naïve patients had a greater mean CRT reduction than those previously treated with any modality (p<0.05) Conclusions: Baseline BCVA and CRT positively influence mean visual and CRT improvement, respectively, after intravitreal bevacizumab in wet AMD. Any prior treatment predicted less CRT reduction.